Pengaruh Self-Enhancement dan Authenticity terhadap Prediksi Diri Masa Depan - Amalia Adhandayani; Bagus Takwin (Lembaga Penelitian Universitas YARSI, 2018)
Future predictions are meaningful for human life. This study aims to examine the effect of self-enhancement on the individual and authentic or unauthentic experiences that individuals have for predicting the future of their lives. In addition, this study is expected to enrich the literature on self-enhancement in Indonesia. This research using experimental method with design of random assignment 2 (self-enhancement: high vs low) x 2 (authenticity: authentic vs. not authentic) and between subjects. 120 participants were included in this study. ANOVA factorial analysis technique was used to see the differences in between tested groups. The results show that people with high self-enhancement have better results in future predictions than people with low self-enhancement. With a distant psychological distance, individuals will be more likely to have more positive predictions of the future, so the high or low level of one's self-enhancement does not impact the future scenario they make. Regardless of authentic or inauthentic experience, the results of this study show that most participants present their future picture optimistically.Furthermore, it is expected in subsequent research to increase the number of participants so that the experimental results can be analyzed more optimally.